2015
DOI: 10.1038/mt.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Variant of Elafin With Improved Anti-inflammatory Activity for Pulmonary Inflammation

Abstract: Elafin is a serine protease inhibitor produced by epithelial and immune cells with anti-inflammatory properties. Research has shown that dysregulated protease activity may elicit proteolytic cleavage of elafin, thereby impairing the innate immune function of the protein. The aim of this study was to generate variants of elafin (GG- and QQ-elafin) that exhibit increased protease resistance while retaining the biological properties of wild-type (WT) elafin. Similar to WT-elafin, GG- and QQ-elafin variants retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…In that study, we found that a more NE-resistant variant of elafin (GG-elafin) could also significantly reduce neutrophil recruitment in a mouse model of LPS-induced lung inflammation compared with WT elafin. 30 However, in contrast to the current SLPI study, we found that GG-elafin did not reduce KC levels. This may be related to the fact that SLPI and elafin have different anti-inflammatory effects.…”
Section: Discussioncontrasting
confidence: 99%
“…In that study, we found that a more NE-resistant variant of elafin (GG-elafin) could also significantly reduce neutrophil recruitment in a mouse model of LPS-induced lung inflammation compared with WT elafin. 30 However, in contrast to the current SLPI study, we found that GG-elafin did not reduce KC levels. This may be related to the fact that SLPI and elafin have different anti-inflammatory effects.…”
Section: Discussioncontrasting
confidence: 99%
“…It was found that aerosolised administration of these recombinant antiproteases reduced the release of a variety of proteases, pro-inflammatory mediators, and in the case of recombinant hMNEI, enhanced bacterial clearance in murine models infected with P. aeruginosa [89][90][91][92]. Subsequent studies have also investigated the therapeutic potential of functional variants of the endogenous antiproteases, elafin and SLPI, and found that these variants retained their antiprotease properties, blunted the pro-inflammatory response to infection in the lung, and showcased an increased resistance to protease-mediated degradation [93,94].…”
Section: Antiprotease Therapiesmentioning
confidence: 99%
“…Proteolytic cleavage of elafin may have implications for its efficacy when being used as a therapeutic in vivo . Recent work has shown that mutating key residues at the NE cleavage site in elafin results in a peptide with similar antiprotease activity as the wild-type form but with significantly increased stability and anti-inflammatory activity [ 101 ]. When compared to wild-type, the mutant forms of elafin were shown to have improved LPS neutralizing activity in vitro and increased anti-inflammatory activity when employed in an acute model of pulmonary inflammation induced by P. aeruginosa LPS [ 101 ].…”
Section: Antiprotease Activity In Cfmentioning
confidence: 99%